Application of the Role Playing Learning Model to Improve Student Learning Outcomes - Isma Aida Fitria; Darmiah (MANDAILING GLOBAL EDUKASIA, 2024)
Every learning process has certain goals and targets. Learning outcomes are one of the targets whose achievements must be evaluated. This research aims to improve student learning outcomes through role playing models. This research is classroom action research. The model used is the Kemmis & Mctaggart model with four steps, namely planning, implementation, observation and reflection. The subjects of this research were elementary school students. Data was collected using observation and test techniques. The data obtained was then analyzed using descriptive statistical techniques and then compared with indicators of research success. The research results show that the role playing model can improve student learning outcomes. This is proven by the increase in student learning outcomes in each cycle, with details in the first cycle the percentage of completion reaching 60% and in the second cycle reaching 80%. This research was stopped in the second cycle because the research success indicators had been achieved. Based on the results of this research, the role playing model can be used as a reference model that can help improve student learning outcomes.